RETRACTED: MENUMBUHKAN MINAT BACA SEJAK DINI DI TAMAN BACA MASYARAKAT - Imam Taulabi; Ali Imron; M. Arif Khoiruddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
This article has besn retracted because it was published in another journal. This article can be found at JOURNAL AN-NAFS: KAJIAN PENELITIAN PSIKOLOGI, VOL. 1 NO. 2 (2016) https://ejournal.iai-tribakti.ac.id/index.php/psikologi/article/view/295